A hydroponic approach to assess the morpho-physiological responses of cotton cultivars under varying vapor pressure deficit conditions - Dhakal, Kripa; Julkowska, Magdalena Maria; Shekoofa, Avat (Frontiers in Plant Science, 2026)
High temperature and water-deficit stresses are among the major limiting factors in cotton (Gossypium hirsutum L.) production. Increasing atmospheric vapor pressure deficit (VPD, kPa) due to global warming further challenges crop productivity by altering plant water balance. This study aimed to assess the effects of different VPD conditions on whole-plant growth characteristics and physiological parameters of new cotton cultivars grown in a hydroponic system. The experiment was conducted from December 2022 to April 2023 at the West Tennessee Research and Education Center (WTREC), University of Tennessee, Jackson, TN. Two Conviron chambers were maintained at two VPD levels (chamber 1, 1.1 kPa and chamber 2, 2.1 kPa, both at 32 °C). Four cotton cultivars DP 2131 B3TXF (Thryvon technology), PHY 400 W3FE, PHY 1140A385–04 W3FE, and PHY 1140B373–04 W3FE were transplanted into hydroponic containers at the cotyledon stage. Cultivar DP 2131 B3TXF exhibited the highest plant height, root length, and total fresh and dry weight in both chambers compared to other cultivars. Under high VPD (2.1 kPa), DP 2131 B3TXF had significantly higher transpiration rate (TR) and stomatal conductance (gs) compared to PHY 400 W3FE. Interestingly, PHY 400 W3FE demonstrated higher intrinsic water use efficiency (iWUE) and significantly lower TR than DP 2131 B3TXF at the same VPD level. The same pattern was observed among cultivars for their stomatal density in chamber 2. These findings indicate that these new cotton cultivars performed differently when comparing TR, stomatal density, and root growth parameters under high VPD conditions. PHY 400 W3FE expressed the limited TR trait, while DP 2131 B3TXF exhibited greater biomass production and root length compared to other cultivars despite reduced root elongation under high VPD conditions.